Reappraisal of the anatomical landmarks of motor and premotor cortical regions for image‐guided brain navigation in TMS practice. Issue 5 (3rd September 2013) - Ahdab, Rechdi; Ayache, Samar S.; Farhat, Wassim H.; Mylius, Veit; Schmidt, Sein; Brugières, Pierre; Lefaucheur, Jean‐Pascal
Abstract Image‐guided navigation systems dedicated to transcranial magnetic stimulation (TMS) have been recently developed and offer the possibility to visualize directly the anatomical structure to be stimulated. Performing navigated TMS requires a perfect knowledge of cortical anatomy, which is very variable between subjects. This study aimed at providing a detailed description of sulcal and gyral anatomy of motor cortical regions with special interest to the inter‐individual variability of sulci. We attempted to identify the most stable structures, which can serve as anatomical landmarks for motor cortex mapping in navigated TMS practice. We analyzed the 3D reconstruction of 50 consecutive healthy adult brains (100 hemispheres). Different variants were identified regarding sulcal morphology, but several anatomical structures were found to be remarkably stable (four on dorsoventral axis and five on rostrocaudal axis). These landmarks were used to define a grid of 12 squares, which covered motor cortical regions. This grid was used to perform motor cortical mapping with navigated TMS in 12 healthy subjects from our cohort. The stereotactic coordinates (x‐y‐z) of the center of each of the 12 squares of the mapping grid were expressed into the standard Talairach space to determine the corresponding functional areas. We found that the regions whose stimulation produced almost constantly motor evoked potentials mainly correspond to the primary motor cortex, with rostral extension to premotor cortex and caudal extension to posterior parietal cortex. Our anatomy‐based approach should facilitate the expression and the comparison of the results obtained in motor mapping studies using navigated TMS. Hum Brain Mapp 35:2435–2447, 2014. © 2013 Wiley Periodicals, Inc.